2009
DOI: 10.1097/mop.0b013e32832c6d2c
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the sex of rearing in the neonate with a disorder of sex development

Abstract: Purpose of review Infants born with ambiguous genitalia [henceforth referred to as Disorder of Sex Development (DSD)] present a unique set of clinical challenges requiring an organized yet practical approach. Given the low frequency with which these types of patients are encountered, their management is best accomplished by practitioners experienced with DSDs. The goal is to discuss, in light of recent publications, information required to make rational management decisions and provide our perspective. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 13 publications
2
17
0
2
Order By: Relevance
“…This is best achieved with early diagnosis, multidisciplinary team management, and good communication between the physician/surgeon and the patients and families [1,2]. Recent studies show that though significant improvement of outcome has been observed with advances in diagnostic testing and genital repair, controversies still exist in the timing for gender assignment and definitive genital reconstruction [1,5,6]. Some authors have suggested delaying gender assignment and genital surgery until the child becomes competent to make his/her own informed decisions [6,7].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is best achieved with early diagnosis, multidisciplinary team management, and good communication between the physician/surgeon and the patients and families [1,2]. Recent studies show that though significant improvement of outcome has been observed with advances in diagnostic testing and genital repair, controversies still exist in the timing for gender assignment and definitive genital reconstruction [1,5,6]. Some authors have suggested delaying gender assignment and genital surgery until the child becomes competent to make his/her own informed decisions [6,7].…”
Section: Introductionmentioning
confidence: 96%
“…However, congenital adrenal hyperplasia (CAH) remains the commonest overall cause of DSD [1][2][3][4]. The cornerstone of management of DSD is thorough investigations to adequately elucidate the nature of the genetic sex, the gonad and the phenotype, and based on this, proper gender is assigned and appropriate genital reconstruction undertaken [1,5]. This is best achieved with early diagnosis, multidisciplinary team management, and good communication between the physician/surgeon and the patients and families [1,2].…”
Section: Introductionmentioning
confidence: 98%
“…It is important to differentiate between 5ARD and AIS as soon as possible so that patients with 5ARD can be raised as boys whenever practical. 12 The penile growth of patients with 5ARD can be promoted by topical DHT treatment and spontaneous virilisation may occur during puberty. Most of these patients who are reared as girls during childhood identify themselves as male and change their gender as an adult, although we have not received any such request from our cohort.…”
Section: Sex Of Rearing Presentationmentioning
confidence: 99%
“…Thus, gender assignment and management of these patients must take into account the family’s sociocultural and religious belief system in addition to the pathophysiology of the disorder [34, 35]. However, it is worth remembering that the framework for decision-making should be based on ethical principles that can transcend all cultural and social mores [36]. Ultimately, we hope that through such efforts our management principles will be guided by robust scientific principles and will ultimately result in better care for all patients with DSD.…”
Section: Discussionmentioning
confidence: 99%